Analysis of the impact of technical and economic parameters on the specific cost of electricity production. (15th March 2018) - Bartnik, Ryszard; Hnydiuk-Stefan, Anna; Buryn, Zbigniew
Abstract: This paper reports the results of analysis of technical and economic parameters on the specific cost of electricity production. The use of a particular technology determines the value of the investment needed for the construction of a power plant, its energy efficiency, internal electrical load of the power plant and its annual operating time. Besides, this cost is considerably dependent on the interest rate on the capital, fuel prices and environmental charges as well as, equally importantly, their variability in time. The variability in the prices of energy carriers and their mutual relations are inevitable for a number of reasons. As shown in the paper the change of the technical parameters in the range of the possible boundaries in a particular technology cannot considerably reduce the specific cost of electricity production. The reduction of the current price relation between gas and three-times cheaper coal (calculated per specific unit of energy) can considerably improve the profitability of the use of the gas-steam technology. When the ratio of the cost of fuel in the specific cost of electricity production is small, the impact of the fuel price on its value is also insignificant. Highlights: Continuous time methodology for calculating specific cost of electricity production. Economic and technical analysis of the cost of electricity production. Price relation between gas and coal on profitability gas-steam technology. The ratio of fuel prices and their impact on the cost of electricity production. Changes in technical parameters slightly reduce the cost of electricity production.